A note on the relationship between COVID-19 and stock market return: evidence from South Asia. Issue 2 (30th August 2021) - Rahman, Md Arafat; Khudri, Md Mohsan; Kamran, Muhammad; Butt, Pakeezah
Abstract : Purpose: The transformation of coronavirus disease (COVID-19) from a regional health crisis in a Chinese city to a global pandemic has caused severe damage not only to the natural and economic lives of human beings but also to the financial markets. The rapidly pervading and daunting consequences of COVID-19 spread have plummeted the stock markets to their lowest levels in many decades especially in South Asia. This concern motivates us to investigate the stock markets' response to the COVID-19 pandemic in four South Asian countries: Bangladesh, India, Pakistan and Sri Lanka. This study aims to investigate the causal impact of the number of confirmed COVID-19 cases on stock market returns using panel data of the countries stated above. Design/methodology/approach: This study collects and analyzes the daily data on COVID-19 spread and stock market return over the period May 28, 2020 to October 01, 2020. Using Dumitrescu and Hurlin panel Granger non-causality test, the empirical results demonstrate that the COVID-19 spread measured through its daily confirmed cases in a country significantly induces stock market return. This paper cross-validates the results using the pairwise Granger causality test. Findings: The empirical results suggest unidirectional causality from COVID-19 to stock market returns, indicating that the spread of COVID-19 has a dominant short-term influence on the stock movements. To the best of the knowledge, this study provides the first empirical insights into the impact of COVID-19 on the stock markets of selected South Asian countries taking the cross-sectional dependence into account. The results are also in line with the findings of other existing literature on COVID-19. Moreover, the results are robust across the two tests used in this study. Originality/value: The findings are equally insightful to the fund managers and investors in South Asian countries. Taking into account the possible impact of COVID-19 on stock markets' returns, investors can design their optimal portfolios more effectively. This study has another important implication in the sense that the impact of COVID-19 on the stock markets of South Asian countries may have spillover effects on other developing or even developed countries.